دور الجامعات الأردنية في مواجهة ظاهرة الإرهاب من وجهة نظر عمداء شؤون الطلبة - عبدالرحيم ربابعة, عمر (جامعة الوادي University of Eloued, 2017)
تهدف هذه الدراسة إلى التعرف على دور الجامعات الأردنية في مواجهة ظاهرة الإرهاب، وكانت عينة البحث عمداء شؤون الطلبة في الجامعات الأردنية، واستخدم الباحث المنــــــهج الوصفي التــــــحليلي كما استخدام المقابلة أداة لجمــــــع المعلومات؛ وللإجــــــــــــــابة على سؤال الدراسة استخدام الباحث التكرارات والنسب المئوية. وتوصلت الدراسة إلى النتائج الآتية: إن هناك ادوار للجامعات لمواجهة الإرهاب حيث بلغت 32 دور ومن أهم الأدوار الحاصلة على أعلى النسب: غرس العقيدة الإسلامية الصحيحة في نفوس الطلبة توعية الطلبة والمجتمع بأخطار الإرهاب، توعية الطلبة بكيفية التعامل مع وسائل الإعلام لبيان الغث من السمين، تضمين المناهج الدراسية مقررات تتحدث عن مخاطر الإرهاب. غرس القيم الروحية والأخلاقية والتربوية النابعة من الإسلام والعروبة. أوصت الدراسة بمجموعة من التوصيات من أهمها: أن يكون هنالك اجتماعا لعمداء شــــــؤون الطلبة في الجامعات الأردنية للاتـــــــــــفاق على وضــــــع خطة لتنفيذها في كل الجامعات لمواجهة ظاهرة الإرهاب. This research aims to find out the role of Jordanian universities in encountering the phenomenon of terrorism. The sample of the study involved the deans of the students Affairs of the Jordanian universities. The researcher adopted the descriptive analytical approach; he also used the interview tool to collect the data. To answer the question of the study, researcher used the frequencies and the percentages .The study came up with the following results: The results indicated that there are roles for universities to encounter terrorism; they amounted to 32. Among the roles of the highest percentages are: implanting proper Islamic faith in the hearts of students. making the students and the community aware of the threats of terrorism. educating students to enable them how to deal the media so that they can differentiate between wheat and chaff. The curriculum should include topics about the dangers of terrorism. Fostering spiritual, moral and educational values hemming from the values of Islam and Arabism .The study concludes with a set of recommendations, the most important of which are: Holding a meeting for the deans of student affairs in the Islamic and Arab universities to agree on a plan to be implemented in all universities to encounter terrorism
مقال
Keywords: الإرهاب؛ دور الجامعات; Rolf Universities ,Terrorism.